2006
DOI: 10.1037/0893-3200.20.4.581
|View full text |Cite
|
Sign up to set email alerts
|

Examining the correlates of psychological aggression among a community sample of couples.

Abstract: In this study, the authors examined the correlates of psychological aggression victimization and perpetration among a community sample of 145 heterosexual couples. For both women and men, psychological aggression victimization was associated with greater psychological distress, anxiety, and physical health symptoms beyond the effects of physical aggression. Psychological aggression victimization was also uniquely associated with higher levels of depression for women. Trait anger and poor relationship adjustmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
112
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 46 publications
(64 reference statements)
15
112
0
2
Order By: Relevance
“…Kim et al (2008) found that men's psychological aggression was negatively associated with their own and their partner's relationship satisfaction. Finally, Taft et al (2006) found that men and women's relationship adjustment were concurrently and negatively related to their perpetration of psychological aggression.…”
Section: Effects Of Psychological and Physical Aggression On Marital mentioning
confidence: 96%
“…Kim et al (2008) found that men's psychological aggression was negatively associated with their own and their partner's relationship satisfaction. Finally, Taft et al (2006) found that men and women's relationship adjustment were concurrently and negatively related to their perpetration of psychological aggression.…”
Section: Effects Of Psychological and Physical Aggression On Marital mentioning
confidence: 96%
“…In- timate partner violence usually co-occurs with psychological aggression, which has recently been shown to be associated with psychological distress and trauma-related symptomatology in both shelter and community samples (Arias & Pape, 1999;Taft et al, 2006). Though research in this area is limited, some recent evidence among women in domestic violence shelters (Levendosky & GrahamBermann, 2001) and partners of abusers in treatment (Panuzio, Taft, Black, Koenen, & Murphy, in press) suggests that interparental psychological aggression may have a robust, unique association with child behavior problems.…”
Section: The Present Study Examined the Relationship Between Intimatementioning
confidence: 99%
“…Other samples reveal that as many as 21% of couples report intimate physical aggression each year (McDonald, Jouriles, Ramisetty-Mikler, Caetano, & Green, 2006). Research has shown that intimate relationship aggression has deleterious mental and physical health consequences for women (Bonomi et al, 2006;Coker, et al, 2002;Loxton, Schofield, & Hussain, 2006), as well as some negative health consequences for men (Coker, et al, 2002;Simonelli & Ingram, 1998;Taft et al, 2006). Assessments of intimate physical aggression based on lifetime incidence or 12-month prevalence data fail to capture the variability in partner aggression across time, particularly for couples in long-term relationships.…”
mentioning
confidence: 99%
“…This distinction theoretically contextualizes aggression in community samples (typically situational couple violence) in relation to more traditional notions of domestic violence (i.e., intimate terrorism), and underscores the importance of examining both husband and wife aggression. This study will also examine emotional or psychological aggression, which some women have reported being even more upsetting than physical abuse they have experienced (Follingstad, et al, 1990), which causes harm, even in the absence of physical aggression (Marshal, 1996;Pico-Alfonso et al, 2006;Taft et al, 2006), and which victims have identified as a primary variable in the assessment of their safety (Cattaneo, 2007). Although most research on emotional aggression has focused on female victims, consistent gender differences have not been found (Coker, et al, 2002;Hamby & Sugarman, 1999;Hines & Saudino, 2003;Swan & Snow, 2002).…”
mentioning
confidence: 99%